Extracorporeal Life Support in Out‐of‐Hospital Refractory Cardiac Arrest. Issue 9 (18th December 2015) - Rousse, Natacha; Robin, Emmanuel; Juthier, Francis; Hysi, Ilir; Banfi, Carlo; Al Ibrahim, Merie; Coadou, Herve; Goldstein, Patrick; Wiel, Eric; Vincentelli, Andre
Abstract: Out‐of‐Hospital refractory Cardiac Arrest (OHrCA) has a mortality rate between 90 and 95%. Since 2009, French medical academic societies have recommended the use of extracorporeal life support (ECLS) for OHrCA. According to these guidelines, patients were eligible for ECLS support if vital signs were still present during cardiopulmonary resuscitation (CPR), or if cardiac arrest was secondary to intoxication or hypothermia (≤32°C). Otherwise, patients would receive ECLS if (i) no‐flow duration was less than 5 min; (ii) time delays from CPR to ECLS start (low flow) were less than 100 min; and (iii) expiratory end tidal CO2 (ETCO2 ) was more than 10 mm Hg 20 min after initiating CPR. We have reported here our experience with ECLS in OHrCA according to the previous guidelines. We retrospectively analyzed mortality rates of patients supported with ECLS in case of OHrCA. From December 2009 to December 2013, 183 patients were assisted with ECLS, among which 32 cases were of OHrCA. Mean age for the OHrCA patients was 43.6 years. Over two‐thirds were male (71.9%). Causes of OHrCA included intoxication, isolated hypothermia <32°C, acute coronary syndrome, pulmonary edema, and other cardiac pathology. Despite adherence to protocols, only two patients (6.2%) with hypothermia and acute myocardium ischemia, respectively, could be discharged from hospital after cardiac recovery. Causes of death were brain death and multiple organ failure. Despite ECLS support setting in accordance with French guidelines in case of refractory OHrCA, mortality rates remained high. French ECLS support recommendations for OHrCA due to presumed cardiac cause should be re‐examined through new studies. Low flow duration should be improved by a shorter time of CPR before hospital transfer.